(untitled) (Al-Academy, 2026)
Visual formation is the aesthetic and artistic phenomenon that the design text produces through the interrelation and engagement of the duality of vision and creative thinking, which is based primarily on two important elements: abstract vision and creative vision. Accordingly, we see that visual formation is a dynamic work that turns into a creative form when it is subjected to visual analysis that merges with creativity when it becomes an aesthetic form from which a color vision emerges that explodes during the creative photography process that the designer seeks. Therefore, the research problem focused on the subject of visual formation in the design of fabrics and cinematic costumes because it is a subject that deserves attention and research. The importance of the research included the intellectual motives that pave the way for students and researchers to know the contents that allow them to realize the living possibilities in the development of the design of fabrics and cinematic costumes, reaching the goal of the research, which was to identify the visual formation in the design of fabrics and cinematic costumes. The research included two topics, the first of which dealt with the concept of visual formation, while the second topic included visual formation in the narrative film. In the third chapter, the American narrative film (The School for Good and Evil) was chosen as a model of films whose actors wear costumes and the type of designed fabrics, as it carries the specifications that it is looking for in its research to achieve the goal that was set to measure the requirements of the research, reaching the fourth chapter, which included the results and conclusions. Keywords: Visual formation - Fabric and costume design - Narrative film.